Governments as owners: State-owned multinational companies - Cuervo-Cazurra, Alvaro; Inkpen, Andrew; Musacchio, Aldo; Ramaswamy, Kannan (Journal of International Business Studies, 2014)
The globalization of state-owned multinational companies (SOMNCs) has become an important phenomenon in international business (IB), yet it has received scant attention in the literature. We explain how the analysis of SOMNCs can help advance the literature by extending our understanding of state-owned firms (SOEs) and multinational companies (MNCs) in at least two ways. First, we cross-fertilize the IB and SOEs literatures in their analysis of foreign investment behavior and introduce two arguments: the extraterritoriality argument, which helps explain how the MNC dimension of SOMNCs extends the SOE literature, and the non-business internationalization argument, which helps explain how the SOE dimension of SOMNCs extends the MNC literature. Second, we analyze how the study of SOMNCs can help develop new insights of theories of firm behavior. In this respect, we introduce five arguments: the triple agency conflict argument in agency theory; the owner risk argument in transaction costs economics; the advantage and disadvantage of ownership argument in the resource-based view (RBV); the power escape argument in resource dependence theory; and the illegitimate ownership argument in neo-institutional theory. After our analysis, we introduce the papers in the special issue that, collectively, reflect diverse and sophisticated research interest in the topic of SOMNCs.